(S)‐3‐aminopiperidine‐2, 6‐dione is a biosynthetic intermediate of microbial blue pigment indigoidine. Issue 2 (21st June 2022) - Zhang, Zhilong; Li, Pengwei; Wang, Min; Zhang, Yan; Wu, Bian; Tao, Yong; Pan, Guohui; Chen, Yihua
Abstract: The biosynthetic investigations of microbial natural products continuously provide powerful biocatalysts for the preparation of valuable chemicals. Practical methods for preparing ( S )‐3‐aminopiperidine‐2, 6‐dione (2 ), the pharmacophore of thalidomide (1 ) and its analog drugs, are highly desired. To develop a biocatalyst for producing ( S )‐2, we dissected the domain functions of IdgS, which is responsible for the biosynthesis of indigoidine (3 ), a microbial blue pigment that consists of two 2 ‐like moieties. Our data supported that the L‐glutamine tethered to the indigoidine assembly line is first offloaded and cyclized by the thioesterase domain to form ( S )‐2, which is then dehydrogenated by the oxidation (Ox) domain and finally dimerized to yield 3 . Based on this, we developed an IdgS‐derived enzyme biocatalyst, IdgS‐Ox* R539A, for preparing enantiomerically pure ( S )‐2 . As a proof of concept, one‐pot chemoenzymatic synthesis of 1 was achieved by combining the biocatalytic and chemical approaches.